2016
DOI: 10.1007/s40534-015-0092-0
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of railway performance: a study of Swedish railway infrastructure

Abstract: The volume of rail traffic was increased by 5 % from 2006 to 2010, in Sweden, due to increased goods and passenger traffic. This increased traffic, in turn, has led to a more rapid degradation of the railway track, which has resulted in higher maintenance costs. In general, degradation affects comfort, safety, and track quality, as well as, reliability, availability, speed, and overall railway performance. This case study investigated the needs of railway stakeholders responsible for analysing the track state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…In [8,35] they correctly state that measurements of track irregularities are based on the assumption that the curvature of the track can be determined by versines. Increased railway traffic leads to the rapid degradation of railway tracks [24], which significantly affects quality, comfort, and safety. The state of a curvilinear section's (the actual circular curve condition with transition curves) geometry is particularly important, especially for tracks in operation, and requires the use of universal and optimal measuring instruments: the solution of this problem is the MMS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In [8,35] they correctly state that measurements of track irregularities are based on the assumption that the curvature of the track can be determined by versines. Increased railway traffic leads to the rapid degradation of railway tracks [24], which significantly affects quality, comfort, and safety. The state of a curvilinear section's (the actual circular curve condition with transition curves) geometry is particularly important, especially for tracks in operation, and requires the use of universal and optimal measuring instruments: the solution of this problem is the MMS.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Douri et al in [24] confirmed that increased traffic has led to an increased rate of degradation of the railway track, which has resulted in higher maintenance costs. Degradation affects comfort, safety, and track quality, as well as reliability, availability, speed, and overall railway performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lost Customer Hours (LCH) within a rail service context]. Rail infrastructure appears to be moving from reactive models of asset maintenance to more 'predict-and-prevent' models where intelligent systems are embedded within the complex socio-technical transport network (Al-Douri et al 2016;Zoeteman 2001Zoeteman , 2006Bousdekis et al 2015;Moore and Starr 2006). Such intelligent infrastructure incorporates the use of remote sensors that provide condition-based maintenance approaches whereby the sensors attached to the assets track asset health data continuously (Bousdekis et al 2015;Campos 2009;Garcí et al 2003;Wang et al 2007).…”
Section: Maintenance Models and Frameworkmentioning
confidence: 99%